A gas-rich disk around DX Cha. Issue Volume 8:Issue S299(2013) (6th January 2014) - Hales, A. S.; De Gregorio-Monsalvo, I.; Montesinos, B.; Casassus, S.; Dent, W. R. F.; Eiroa, C.; Hughes, A. M.; Garay, G.; Mardones, D.; Ménard, F.; Palau, A.; Pérez, S.; et al.
Abstract: DX Cha (HD 104237) is a southern, optically bright Herbig Ae star with an infrared excess, that is part of a small stellar group younger than 5 Myr. We used the APEX and ASTE submillimeter telescopes in Chile to search for continuum and gas emission around this system. Using LABOCA on APEX we detect strong continuum emission around HD104237-A and system component HD104237-E. Our ASTE spectrum detects a double-peaked 12 CO(3-2) line profile towards the system, typical of a rotating disk. The new data are used as constraints with MCFOST to produce a disk model that fits the entire SED as well as the observed CO line profile.